Pemanfaatan Media Pasir Untuk Meningkatkan Kemampuan Menulis Anak Usia 5-6 Tahun - Wulandari, Catur (Generasi Emas, 2024)
This research aims to improve the pre-writing skills of early childhood by using sand media. The research method used is the classroom action research (PTK) method which is carried out in stages, namely planning, taking action, observing and analyzing or reflecting. The subjects of this research were 15 children aged 5-6 years in one of the schools in the city of Jakarta. Sand media was chosen because it has a texture and properties that can stimulate children's motor sensors and is expected to help children develop pre-writing skills. The results of the research show that children's writing skills in the initial conditions and cycle I have not reached the performance indicators. The results of research in the second cycle show that the use of sand media can significantly improve children's pre-writing abilities, as seen from the increase in accuracy and neatness and the shape of the letters they make. Thus, sand media can be used as an effective alternative in learning pre-writing in early childhood education.